Demographic Characteristics and Etiology of Simple Mandibular Angle Fracture: Experience of 30 Cases in Dhaka City - Goswami, Uday Kumar; Das, Binay Kumar; Dash, Prodip Chandra; Islam, Md Razaul (Journal of Current and Advance Medical Research, 2018)
Background: Simple mandibular angle fracture can occur in different group of people due to different etiology. Objective: The purpose of the present study was to find out the demographic characteristics and etiology of simple mandibular angle fracture. Methodology: This cross-sectional study was conducted in the Department of Oral and Maxillofacial Surgery at Dhaka Dental College & Hospital, Dhaka and Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from January 2010 to December 2010 for a period of one (01) year. Among all patients admitted/attended to the hospital IPD or OPD with fracture of mandibular angle with or without other associated fracture sites were selected as study subjects. The details of demographics characteristics and etiology of fracture were recorded. Result: A total number of 30 patients were recruited for this study. Majority of the respondents 21(70%) were male and rest 09(30%) were female. Mean age of the patients was 29.5±6.795 years. Among the 30 respondents 46.7% had history of Road Traffic Accident, 43.3% due to assault and only 10% for other causes. Conclusion: In conclusion the most common etiology of mandibular angle fracture is road traffic accident. Male and younger adult are frequently encounter the mandibular angle fracture. Journal of Current and Advance Medical Research 2018;5(2):45-48